The Moderating Effect of Audit Quality on the Links Between Stock Market Segmentations, Surplus Free Cash Flow, and Income-increasing Discretionary Accruals - Ahmad A. Toumeh; Sofri Yahya; Mohammed M. Yassin; Maha D. Ayoush (Australasian Accounting, Business and Finance Journal, 2021)
The objective of this paper is to examine the impacts of stock market segmentations (SMS) and surplus free cash flow (SFCF) on income-increasing discretionary accruals. The study also provides the initial evidence regarding the influence of audit quality (AQ) as a moderating variable on those relationships. A sample of non-financial firms was taken from the list of Amman Stock Exchange over the period 2013-2019. Using Huber-White’s sandwich estimator for pooled OLS regression, the current research presents empirical evidence harmonious with the prediction in all hypotheses. Further, the findings document that a Big 4 auditor weakens the SMS-DAC and SFCF-DAC associations, which suggests that the role of Big 4 audit firms is effective in mitigating management’s opportunistic behaviour. However, the reported results provide beneficial information to investors, regulators, external auditors, policymakers, shareholders, and other countries with similar institutional environment.
Keywords: Audit quality; Jordan; Discretionary accruals; Earnings management; Surplus free cash flow.